Šport na Fakulteti za družbene vede od začetka do danes - Štekl, Jaroš (Šport (Ljubljana), 2019)
Sports plays a special role in every lifetime, and no other way is it in the student era. Studying at faculties is the last stage of education for most people, and it is even more important that sport at the University is maintained and developed. At the Faculty of Social Sciences, the form of sports education for students changed over time. Everything from compulsory regular sports education in all years of study, to the optional subject of Sports Education, and recreational training for students. University sport competitions have also been and continue to be one of the forms of sports activity of FDV students. Care is also taken for employees who, in addition to sports days, also have regular sports and recreational exercise. Given the fact that sports or sports education at Slovene universities has been present for quite some time but in various forms, it would make sense to systematically regulate sports activities for students of all Slovenian universities and their faculties.
Keywords: Faculty of social sciences; Fakulteta za družbene vede; physical education; razvoj; sport; sport development; students; šport; športna vzgoja; študenti; University of Ljubljana; Univerza v Ljubljani